Analisis Return On Equity Pada KPRI ”SEHATI” - Shalihin, Muhammad; Nurulrahmatiah, Nafisah (MOTIVASI, 2020)
Purpose – The purpose of this study was to determine the amount of ROE on KPRI "SEHATI".Design/methodology – This type of research is a type of descriptive research that is knowing how much Return on Equity (ROE) on KPRI "SEHATI". The population used in this study is the balance sheet financial statement data for 10 years. And the sample used in the form of 2014-2018 balance sheet financial statement data consists of data of own capital / net worth and the remaining operating results. The sampling used is purposive sampling, with consideration lies in the availability of data and the use of the latest data (update). The data analysis technique used is the One Sample T-test.Findings - The results showed that the Return On Equity (ROE) on the KPRI "SEHATI" averaged 14.32% or said to be good enough, above the research standards studied, 9 to <15%. The conclusion of this study is the ROE of the "SEHATI" KPRI for the 2014-2018 period is said to be quite good with an average ROE of 14.32%.